Rituals of worship towards Goddess Yanzhima in the Barguzinsky District of the Republic of Buryatia - Lygdenova, Viktoria V. (The New Research of Tuva, 2015)
Annual three days rituals of worship towards Buddhist goddess Yanzhima in the Barguzinsky and Kurumkansky districts of the Republic of Buryatia are considered in the article: the ritual of worship towards water spirits "LusuudTakhilga”, the ritual of worship towards the owner of the mountain "Barkhan-Uul”, praying and worship towards Goddess Yanzhima and the celebration of her appearance on the sacred stone.